1) 2 1/3 is also equal to 7/3
4 1/5 is also equal to 21/5
you need to make the denominators the same so you have to find the lowest common multiple, which is 15 since both 5 and 3 can be times by to make 15
you need to also times the numerators by the number you're timesing the denominator by
7/3 x 5 = 35/15
21/5 x 3 = 63/15
now add those together
35/15 + 63/15 = 98/15
now just convert 98/15 back to a mixed fraction
98/15 = 6 8/15
the answer is..
I'll do the others in a different answer!!
Answer:
<em>x = 30.2 units</em>
Step-by-step explanation:
<u>Trigonometric Ratios</u>
The ratios of the sides of a right triangle are called trigonometric ratios.
Selecting any of the acute angles, it has an adjacent side and an opposite side. The trigonometric ratios are defined upon those sides and the hypotenuse.
The given right triangle has an angle of measure 51° and its adjacent leg has a measure of 19 units. It's required to calculate the hypotenuse of the triangle.
We use the cosine ratio to calculate x:
Solving for x:
x = 30.2 units
Answer:
3/11
3:11
Step-by-step explanation:
Answer:
a) 1/22
b) 3/44
c) 3/11.
Step-by-step explanation:
a).
Prob(picking a blue first) = 5/12.
Prob(picking a yellow next) = 4/11 ( as it is without replacement)
Prob(purple next) = 3/10
Probability of picking these in this order = 5/12 * 4/11 * 3/10
= 1/22 (answer).
Note the probabilities are multiplied because the 3 events are independent.
b)
Prob(all the same colour) = Prob(All are blue) + Prob(all are yellow) + Prob ( All are purple)
Prob(All are blue) = 5/12 * 4/11 * 3/10 = 1/22
Prob(all are yellow) = 4/12 * 3/11 * 2/10 = 1/55
Prob(all purple) = 3/12 * 2/11 * 1 /10 = 1/220
So probability there are all the same colour = the sum of the above
= 3/44 (answer).
c) I take this to mean that all 3 are a different colour.
This will be the number of combinations of blue, yellow and purple possible which is 3! = 6.
So the answer is 6 * 1/22 = 3/11.
Answer:
(1, 2 )
Step-by-step explanation:
x + y = 3 (subtract x from both sides )
y = 3 - x → (1)
2x - y = 0 → (2)
Substitute y = 3 - x into (2)
2x - (3 - x) = 0
2x - 3 + x = 0
3x - 3 = 0 ( add 3 to both sides )
3x = 3 ( divide both sides by 3 )
x = 1
Substitute x = 1 into (1)
y = 3 - 1 = 2
solution is (1, 2 )